60 years of advances in neuropsychopharmacology for improving brain health, renewed hope for progress - Millan, Mark J.; Meyer-Lindenberg, Andreas (European neuropsychopharmacology, 2015)
Pharmacotherapy is effective in helping many patients suffering from psychiatric and neurological disorders, and both psychotherapeutic and stimulation-based techniques likewise have important roles to play in their treatment. However, therapeutic progress has recently been slow. Future success for improving the control and prevention of brain disorders will depend upon deeper insights into their causes and pathophysiological substrates. It will also necessitate new and more rigorous methods for identifying, validating, developing and clinically deploying new treatments. A field of Research and Development (R and D) that remains critical to this endeavour is Neuropsychopharmacology which transformed the lives of patients by introducing pharmacological treatments for psychiatric disorder some 60 years ago. For about half of this time, the European College of Neuropsychopharmacology (ECNP) has fostered efforts to enhance our understanding of the brain, and to improve the management of psychiatric disorders. Further, together with partners in academia and industry, and in discussions with regulators and patients, the ECNP is implicated in new initiatives to achieve this goal. This is then an opportune moment to survey the field, to analyse what we have learned from the achievements and failures of the past, and to identify major challenges for the future. It is also important to highlight strategies that are being put in place in the quest for more effective treatment of brain disorders: from experimental research and drug discovery to clinical development and collaborative ventures for reinforcing “R and D”. The present article sets the scene, then introduces and interlinks the eight articles that comprise this Special Volume of European Neuropsychopharmacology. A broad-based suite of themes is covered embracing: the past, present and future of “R and D” for psychiatric disorders; complementary contributions of genetics and epigenetics; efforts to improve the treatment of depression, neurodevelopmental and neurodegenerative disorders; and advances in the analysis and neuroimaging of cellular and cerebral circuits.